Utilization of Used Vegetable Oil as a Biodiesel Fuel - Mohammed, Ehsan B.A.; Yassin, Atif A.A.; Abdelrahman, Maha A.A.; Abdou, Abdelnasir M. (Gezira Journal of Engineering and Applied Sciences, 2020)
In this study the reusing of vegetable oil as an alternative substitute for biodiesel was investigated. The used vegetable oil (UVO) was obtained from Baraka Factory – Potato chips line, Wad Madani, Sudan. The biodiesel is produced from used vegetable oil by alkali transesterification. The kinematic viscosity of biodiesel (at 40ºC), flash point, density (at 15ºC), and calorific value were 5.35cSt, 119ºC, 0.881gm/ml, and 41.9MJ/kg respectively. The results showed that the used vegetable oil is suitable for biodiesel production